Wysokie krzyże irlandzkie i ich związki z mitologią (VIII-XII wiek) - Bulas, Ryszarda (Vox Patrum, 2003)
The Celtic Crosses are an original phenomenon that unites in itself spiritual traditions of the East and artistic heritage of the West. The original basic shape of the idea is Indo-Iranian and it was close to Celtic mentality. Old myths were translated into a symbolic language of art. The particular feature of the Celtic Cross is the co-existence of Nature and Bible, Myth and Christology.